اجراءات المتابعة الخاصة لجرائم الفساد - زغبة سارة (جامعة المسيلة, 2020)
أصبحت ظاهرة الفساد من القضايا الراهنة على الساحة الدولية والمحلية باعتبارها تشكل عائقا أساسي للتنمية في مختلف مجالاتها. و لهذا عمل المشرع الجزائري نتيجة لتفاقم هذه الظاهرة و اتساع نطاقها ، إلى أفراد جرائم الفساد في قانون خاص مستقل و تم إحالة الجرائم من قانون العقوبات إلى قانون الوقاية من الفساد و مكافحته 06-01 ، بالإضافة إلى استحداثه لجرائم جديدة لم تكن موجودة من قبل في قانون العقوبات مما يفرض خصوصيات في النظام الإجرائي و العقابي لهذه الجرائم . وحرصا من الجزائر على مواكبة التشريعات الدولية، و انضمامها إلى معظم الاتفاقيات الدولية لمكافحة الفساد ، فإنها سعت من خلال ذلك إلى نص العديد من القوانين في مجال محاربة الفساد و مكافحته ، إضافة إلى تعيين قوانينها أو بالأحرى منظومتها القانونية لتتماشى مع النصوص و الاتفاقيات الدولية و إنشاء العديد من الهيئات المتخصصة في محاربة الفساد و فرض إجراءات صارمة للكشف عن بؤر الفساد و القضاء عليها . الكلمات المفتاحية: الفساد، جرائم ، قانون،النظام الاجرائي Summary: The phenomenon of corruption has become one of the current issues on the international and domestic arena, as it constitutes a major obstacle to development in its various fields. This is why the Algerian legislature worked as a result of the exacerbation of this phenomenon and its expansion, to individuals of corruption crimes in a special and independent law. The crimes were referred from the Penal Code to the Law on Prevention and Combating Corruption 01/06, in addition to its introduction of new crimes that did not exist before in The Penal Code imposes peculiarities in the procedural and punitive system for these crimes. Algeria's keenness to keep abreast of international legislation and its accession to most international anti-corruption conventions, it has sought through this to stipulate many laws in the field of fighting and combating corruption, in addition to defining its laws or rather its legal system in line with international texts and conventions and establishing Many bodies specialized in fighting corruption and imposing strict procedures to uncover and eliminate hotbeds of corruption. contre la corruption et imposer des procedures strictes pour découvrir et éliminer les foyers de corruption. Key words: corruption, crimes, law, procedural system
Keywords: الفساد، جرائم ، قانون،النظام الاجرائي